Unpacking "Health Reform" and "Policy Capacity"; Comment on "Health Reform Requires Policy Capacity" - David Legge; Deborah H Gleeson (Kerman University of Medical Sciences, 2015)
Health reform is the outcome of dispersed policy initiatives in different sectors, at different levels and across time. Policy work which can drive coherent health reform needs to operate across the governance structures as well as the institutions that comprise healthcare systems. Building policy capacity to support health reform calls for clarity regarding the nature of such policy work and the elements of policy capacity involved; and for evidence regarding effective strategies for capacity building.